The Crisis and Job Guarantees in Urban India - Swati Dhingra; Stephen Machin (Institute of Labor Economics (IZA), 2020)
This paper uses a new field survey of low-wage areas of urban India to show that employment and earnings were decimated by the lockdown resulting from the Covid-19 crisis. It examines workers' desire for a job guarantee in this setting. Workers who had a job guarantee before the crisis were relatively shielded by not being hit quite so hard in terms of the increased incidence of job loss or working zero hours and earnings losses. A stated choice experiment contained in the survey reveals evidence that low-wage workers are willing to give up around a quarter of their daily wage for a job guarantee. And direct survey questions corroborate this, with informal, young and female workers being most likely to want a job guarantee, and to want it even more due to the current crisis.
Keywords: J46; J68; L52; P25; 330; job guarantee; India; urban labour markets; job vignettes; COVID-19